A study of piglets born by spontaneous parturition under uncontrolled conditions: could this be a naturalistic model for the study of intrapartum asphyxia? - Trujillo-Ortega, M.E.; Mota-Rojas, D.; Olmos-Hermàndez, et al., A. (Acta Biomedica Atenei Parmensis, 2007)
In order to evaluate how spontaneously born piglets could be a suitable model for the study of intrapartum hypoxia, 230 newborn piglets were studied. Out them, 8.3% (n = 19) died intrapartum, 21.7% (n = 50) were born with moderate-to-severe intrapartum hypoxia, and 70% (n = 161) were born with mild or no evidence of intrapartum distress. Piglets born without any evidence of intrapartum asphyxia weighed approximately 240 g lower than those born with intrapartum hypoxia and intrapartum-dead piglets (P